Dual source computed tomography in patients with congenital heart disease - Ihlenburg, Katharina Susanne; Rompel, Oliver; Rueffer, Andre; Purbojo, Ariawan; Cesnjevar, Robert; Dittrich, Sven; Glöckler, Martin (Thoracic and Cardiovascular Surgeon, 2014)
The objective of this study was to review our early experience with the dual source computed tomography (DSCT), a recently available scanner technique equipped with two X-ray tubes and two detectors, in the context of congenital cardiac malformations.We reviewed 40 pediatric patients with congenital heart disease (CHD) who underwent DSCT between September 2009 and December 2011 as diagnostic imaging tool for surgical procedures.The median age was 0.36 years (range: 3 days to 44 years). Great vessels (n = 13), cardiac anatomy (n = 13), trachea and vascular rings (n = 7), pulmonary veins (n = 4), and coronary arteries (n = 3) were focused on, which revealed important information for surgery. Scanning quality was affected in only two cases (metal artifacts and tachycardia). Overall median age-specific dose was 1.47 mSv. In patients younger than 1 year (n = 26), median dose was 1.28 mSv.DSCT allows a very rapid scan speed, examinations are performed in spontaneously breathing patients, and the radiation exposure is relatively low. It is very valuable in the setting of complex surgery by revealing the position of anatomical structures in their relation to each other. Missing information can be acquired less invasively in addition to echocardiography and might replace cardiac catheterization for several morphological indications.
EVALuna2:14356

Migration von Weichmachern und Beschichtungen während der extrakorporalen Perfusion in der Kardiotechnik - Münch, Frank; Göen, Thomas; Schulbert, Christian; Cesnjevar, Robert; Ihlenburg, Katharina Susanne (Abstracts der 40. Internationalen Jahrestagung der DGfK und 3. Fokustagung Herz, 2011)
UnivIS-Import:2017-12-18:Pub.2011.nat.dgeo.IGM.LP.migrat

Preoperative assessment of the aortic arch in children younger than 1 year with congenital heart disease: utility of low-dose high-pitch dual-source computed tomography. A single-centre, retrospective analysis of 62 cases - Glöckler, Martin; Halbfass, Julia; Koch, Andreas; Dittrich, Sven; Achenbach, Stephan; Rueffer, Andre; Ihlenburg, Katharina Susanne; Cesnjevar, Robert; May, Matthias; Uder, Michael; Rompel, Oliver (European Journal of Cardio-Thoracic Surgery, 2014)
To evaluate the feasibility, image quality and impact of 3D imaging in low-dose high-pitch dual-source computed tomography (DSCT) to assess arbitrary anatomical malformations of the aortic arch in children <1 year of age with congenital heart disease (CHD).Between January 2010 and May 2013, DSCT was performed to assess the aortic arch anatomy in a total of 62 consecutive patients with CHD (aged 0-348 days). DSCT was used whenever conventional echocardiography was not sufficient to display the complex anatomy entirely. Image data acquisition was realized within a single cardiac cycle using prospective ECG triggering. 3D reconstruction for surgical planning was performed. Image quality was assessed retrospectively, using a 4-point scale from '1 = no artefacts' to '4 = uninterpretable'. The accuracy and impact of the 3D reconstructions was compared with intraoperative findings using a 5-point scale (from '1 = essential' to '5 = misleading'). Administered radiation exposure was evaluated.Imaging was successful in all patients, image quality was rated 1.34 on the 4-point scale and the impact of the 3D reconstructions for surgical planning was 2.05 on the 5-point scale. Mean dose-length product was 6.8 ± 2.6 mGy cm, and the effective dose was 0.45 ± 0.13 mSv (0.21-0.74).DSCT is a fast and appropriate imaging modality in the preoperative assessment of the aortic arch for surgical planning in CHD.
EVALuna2:11864